Improving Students' Ability In Writing Recount Text By Using Picture Series (A Classroom Action Research at Eighth Grade of SMP Negeri 2 Mondokan, Sragen in 2011/2012 Academic Year) - Jumadilah, Siti; , Prof. Dr. Sri Samiati Tarjana; , Drs. Sigit Haryanto, M.Hum (2013)
This study is based on the needs to improve the students' ability in writing recount text. Therefore, it is designed to improve the students' writing skill especially in writing recount text through the use of picture series technique. In this technique, the students practice writing recount text based on the picture series given. This technique is believed to improve the students' writing ability and their involvement in the teaching and learning process. This study constitutes a classroom action research. Employing an action research design, it was conducted collaboratively with a fellow English teacher in observing the implementation of the technique. This study was conducted in two cycles. Each cycle encompassed three meetings. The subjects of the study are the eighth grade students of SMP Negeri 2 Mondokan Sragen. The findings of the study indicated that picture series media was successful in improving the students' ability in writing recount text as well as increasing their involvement in the teaching and learning process. It can be seen from the percentage of students' who gained scores set in the criteria of success which was at least 6.5. In the first cycle, only 21 students (56.7%) of the students gained scores higher than and/or equal to 6.5. Meanwhile in second cycle, 37 students (100%) of the students gained scores higher than and/or equal to 6.5. Besides, the finding indicated that picture series media was effective in enhancing the students' involvement in the writing activities, especially when they worked in groups. With the findings above, it can be inferred that picture series media has been proven to improve not only the students' ability in writing recount text but also the students' involvement in the teaching and learning process, particularly in writing recount text. Therefore, it is suggested that English teachers apply this technique as one of the alternatives that can be used in teaching recount skill. For next researchers, it is recommended to do further research about the use of picture series in the teaching of English which focus on improving students' grammar mastery. The use of picture series is beneficial not only in improving the students' ability in writing recount text but also the students' involvement in the teaching and learning process, it is advisable that this technique be used by students as their learning strategy to practice their recount text ability, and even more to practice their writing skill as well. Therefore, teachers should always try to create interesting picture series and text for their teaching. Based on the result, teachers can apply recount text to improve the students' ability in writing recount text.